A plasma generator based on nonself-sustained low-pressure glow discharge with a large-volume hollow cathode; Instruments and Experimental Techniques; Vol. 54, № 1 - Lopatin I. V.; Akhmadeev Y. K.; Koval N. N. Nikolay Nikolaevich; Shchanin P. M. (2011, 2011)
Title screen